State‐of‐the‐art and ‐practice review of public transport priority strategies. Issue 4 (1st May 2015) - Diakaki, Christina; Papageorgiou, Markos; Dinopoulou, Vaya; Papamichail, Ioannis; Garyfalia, Malandraki
Abstract : In the years to come, public transport (PT) will be called to play a significant role towards achieving the sustainable transport system objective set for the future in Europe and beyond. To this end, the quality, accessibility and reliability of its operations should be improved. In this context, the favourable treatment of PT means within the road network may have, among others, a significant contribution. Such treatment can be derived as a result of an appropriate design of the road network facilities and/or the employed signal control at the network junctions. To this end, several approaches have been proposed, and it is the aim of this study to review the state‐of‐the‐art and ‐practice in such approaches, focusing mainly on those attempting to provide priority via appropriate adjustment, in real time, of the junctions' signal control.